Fabrication of automotive clutch demonstration models / Ihsan Syadid Mohd Azmi, Ismarullizam Mohd Ismail and Mohd. Zaidi Zawawi - Mohd Azmi, Ihsan Syadid; Mohd Ismail, Ismarullizam; Zawawi, Mohd. Zaidi (2000)
To begin this fabrication of automobile clutch demonstration models project, there are several important things that must be considered. Doing the technical work is the most important aspect of this work. Our main objectives of this work is to fabricate the following three types of models: viz., the manual clutch, torque converter, and semi-automatic clutch (motorcycle clutch). Besides that, we have to learn about the installation and inspection of all these fluid, dry, and wet clutches. On this fabrication project, we start with disassembling and overhauling all the models with the right method carefully. Servicing the parts will give us knowledge about the parts, their functions, and their designs.